Structural properties in barium titanate using modifiers for piezoelectric effect - Mendoza Ochoa, Carlos Alfredo (2025)
Barium Titanate (BaTiO₃) is a perovskite considered one of the most promising materials of the twenty-first century. Its BaTiO₃ structure is known to be the most versatile ceramic host. This research focuses on studying the Barium Titanate (BaTiO₃) perovskite structure using modifiers such as CaCO₃ and LiCl at 3 wt%, 5 wt%, and 7 wt% to analyze the changes in phase transition at 700°C, 1000°C, and 1200°C. Additionally, all structures are analyzed by Scanning Electron Microscopy to observe changes in grain size at different sintering temperatures, using only 7 wt% of modifiers. The Archimedes method is also employed to study changes in porosity at different phases of BaTiO₃ with 3 wt% and 7 wt% of LiCl and CaCO₃ to better understand the BaTiO₃ structure for future energy conversion systems utilizing piezoelectric properties. This research may inspire novel designs where the piezoelectric effect is used as the primary source of energy.